CO2 reforming of methane combined with steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal-oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C. (Applied Energy, 2006)
CO2 reforming with simultaneous steam reforming or partial oxidation of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst (prereduced by H-2) at different process conditions has been investigated. In the simultaneous CO2 and steam reforming, the conversion of methane and H2O and also the H-2/CO product ratio are strongly influenced by the CO2/H2O feed-ratio. In the simultaneous CO2 reforming and partial oxidation of methane, the conversion of methane and CO2, H-2 selectivity and the net heat of reaction are strongly influenced by the process parameters (viz. temperature, space velocity and relative concentration of O-2 in the feed). In both cases, no carbon deposition on the catalyst was observed. The reduced NdCoO3 perovskite-type mixed-oxide catalyst (Co dispersed on Nd2O3) is a highly promising catalyst for carbon-free CO2 reforming combined with steam reforming or partial oxidation of methane to syngas. (c) 2005 Published by Elsevier Ltd.
Keywords: Co/Nd2O3 catalyst; methane; NdCoO3 perovskite-type mixed metal-oxide catalyst; Oxy-CO2 reforming of methane; simultaneous CO2 and steam reforming of methane

Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation

Oxy-CO2 reforming of methane to syngas over CoOx/MgO/SA-5205 catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Fuel, 2006)
The OXY-CO2 methane reforming reaction (OCRM) has been investigated over CoOx supported on a MgO precoated highly macroporous silica-alumina catalyst carrier (SA-5205) at different reaction temperatures (700-900 degrees C), O-2/CH4 ratios (0.3-0.45) and space velocites (20,000-100,000cc/g/h). The reaction temperature had a profound influence on the OCRM performance over the CoO/MgO/SA-5205 catalyst; the methane conversion, CO2 conversion and H-2 selectivity increased while the H-2/CO ratio decreased markedly with increasing reaction temperature. While the O-2/CH4 ratio did not strongly affect the CH4 and CO2 conversion and H-2 selectivity, it had an intense influence on the H-2/CO ratio. The CH4 and CO2 conversion and the H-2 selectivity decreased while the H-2/CO increased with increasing space velocity. The O-2/CH4 ratio and the reaction temperature could be used to manipulate the heat of the reaction for the OCRM process. Depending on the O-2/CH4 ratio and temperature the OCRM process could be operated in a mildly exothermic, thermal neutral or mildly endothermic mode. The OCRM reaction became almost thermoneutral at an OCRM reaction temperature of 850 degrees C, O-2/CH4 ratio of 0.45 and space velocity of 46,000 cc/g/h. The CH4 conversion and H-2 selectivity over the CoO/MgO/SA-5205 catalyst corresponding to thermoneutral conditions were excellent: 95% and 97%, respectively with a H-2/CO ratio of 1.8. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: methane; oxy-CO2 reforming; Syngas

Partial oxidation of methane to syngas with or without simultaneous steam or CO2 reforming over a high-temperature stable-NiCoMgCeOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Applied Catalysis A-General, 2006)
A NiCoMgCeOx (Ni/Co/Mg/Ce: 1:0.2:1.2:1.2)/zirconia-hafnia catalyst with unusually high thermal stability has been investigated for syngas generation via a process that includes the catalytic partial oxidation of methane (CPOM), the oxidative steam reforming of methane (OSRM) and the oxidative CO2 reforming of methane (OCRM). The catalyst calcined at 1400 degrees C (for 4 h) showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions; furthermore no catalyst deactivation was observed for a period of 20 h. For the CPOM process, the selectivity for H-2 was > 95% at reaction temperatures > 650 degrees C however temperatures above 800 degrees C were required to achieve > 95% CO selectivity. While the reaction temperature had a considerable influence on the CPOM product H-2/CO ratio, the space velocity (at 850 degrees C) did not affect it to any significant extent. For the OSRM process, the H2O/CH4 ratio and the reaction temperature had a strong effect on the product H-2/CO ratio and the heat of the reaction; depending on the H2O/CH4 ratio and reaction temperature, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion was very strongly affected by the reaction temperature in the OCRM process; reasonably high CO2 conversion ( > 40%) could only be obtained at high OCRM reaction temperatures ( > 850 degrees C). The exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: dry (CO2) reforming; high-temperature stable; methane; oxy-steam reforming; Partial oxidation; Steam reforming; Syngas

Oxy-methane reforming over high temperature stable NiCoMgCeOx and NiCoMgOx supported on zirconia-haffnia catalysts: accelerated sulfur deactivation and regeneration - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Catalysis Communications, 2007)
NiCoMgOx and NiCoMgCeOx on commercial low surface area zirconia-haffnia catalysts have unusually high thermal stability (>= 2000 degrees C) for syngas generation via the methane partial oxidation process (J. Catal., 233, 36, 2005). Herein we report the results on accelerated sulfur deactivation (0.74 mol% sulfur in feed) and corresponding regeneration (at 800 degrees C in 1:1 O-2 + N-2 flow) over these catalysts. The NiCoMgCeOx catalyst, due to a larger mobility of lattice oxygen, showed a considerably higher resistance to sulfur poisoning; the higher mobility of the lattice oxygen in case of the NiCoMgCeOx catalyst may be related to the presence of CeO2. During the deactivation process, the selectivity for H-2 was decreased to a much greater extent than that for CO. Regeneration studies showed that even after complete deactivation of the catalysts, the original activity/selectivity of both the catalysts could be completely restored after a simple regeneration process. Based on their exceptionally high thermal stability, high activity/selectivity and easily regenerability, the NiCoMOx, and NiCoMgCeOx catalysts appear to be very promising candidates for the CPOM process. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Deactivation; high temperature stable; methane; Partial oxidation; Regeneration; Sulfur